Sistema de visión subacuático inalámbrico usando un algoritmo de compresión progresivo con región de interés - Rubino, Eduardo M. (2018)
The increasing demand for underwater robotic intervention systems around the world in several application domains requires more versatile and inexpensive systems. By using a wireless communication system, supervised semi-autonomous robots have freedom of movement and, at the same time, allows the operator to get camera feedback and supervise the intervention. On the other hand, the typical data rate of the wireless submarine channels is generally very limited, requiring the application of advanced compression techniques. In this paper we present the DEBT (Depth Embedded Block Tree) algorithm for the progressive compression of images with region of interest (ROI). The results demonstrate advantages with other compression algorithms, and the possibility of executing the algorithm in real time on ARM-based embedded low-power computers.